Isolation and identification of fungi associated of growth of onion with it types white,yellow,green and red that grassed in regions surrounded of Al-Qadisia - Yas Lahmood, Walaa; Foad Manher, Luma (Al-Qadisiyah Journal of Pure Science, 2018)
This study included obtained random samples of onion product with complete parts of it ,roots,stems and leaves from places that culture with onion that belong to Al- Qadisia ,these samples included the four types of onion,white,yellow,green and red. The parts of onion were cultured in the lab on medium potato dextrose agar (PDA) in dispossoble petri dish,after growth of fungi the species of fungi are identified and the percentage frequency of each fungus were calculate .The fungi Alternaria alternate gived higher percentage frequency from other fungi it about %66.66 in the red onion roots the second fungus is Aspergillus niger the percentage frequency about %43.47 in yellow onion roots ,in fungus Fusarium oxysporium the percentage frequency is %33.33 in red onion roots .The onion stems ,the higher number record from fungus Penicillium notatium is about %38.88 in yellow onion stem ,the second fungus was Alternaria tenussimia about %32 in white onion stem ,many numbers observed that isolated from onion leaves like Curvularia lunata,the percentage frequency about %52.63 from the white onion leaves while the fungus Alternaria alternate recorded %23.07 in green onion leaves and the fungus Penicillium notatium record %21.05 from white onion leaves .